HUBUNGAN POLA MAKAN DENGAN KEJADIAN GASTRITIS DI DESA KOPIWANGKER - Waworuntu, Elshadai Teovilia; Pangemanan, Damajanty; Natalia, Adriani (JURNAL KEPERAWATAN, 2024)
Background: Diet is one of the factors that can affect the incidence of gastritis. Implementation of a good diet is needed because one of the causes of gastritis is how to manage diet. Objective: to determine the relationship between diet and the incidence of gastritis in Kopiwangker Village. Method: This study uses a quantitative design approach cross sectional Sample taken using techniq use purposive sampling and obtained a total sample of 87 respondents. Results: research using test chi square obtained a significant value of 0.000 or less than a (p <0.05), Conclusion: there is a relationship between diet and the incidence of gastritis in Kopiwangker Village. Suggestion: it is hoped that the community can pay attention to healthy eating patterns and health workers are advised to provide health education in the form of counseling to improve healthy eating patterns so as to prevent the chances of gastritis occurring.